2013
DOI: 10.2214/ajr.12.10171
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Conventional MRI Sequences and Diffusion-Weighted Imaging in Differentiating Malignant From Benign Portal Vein Thrombus in Cirrhotic Patients

Abstract: Signal-intensity characteristics on DWI and measured ADC values do not reliably differentiate benign PVT from malignant PVT. On the other hand, careful assessment of conventional MRI findings may allow this distinction, thus obviating biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 27 publications
3
49
0
2
Order By: Relevance
“…The high SI of the DVT on DWI was compatible with that of a cerebral vein thrombus 2 and over half of the portal vein thrombi. 3 These results suggest that the high SI of venous thrombi on DWI is a characteristic finding. However, the sensitivity and specificity of combined DWI/T 2 -weighted MR imaging were better than those of DWI alone as a screening tool for detecting abdominal malignancies.…”
mentioning
confidence: 78%
“…The high SI of the DVT on DWI was compatible with that of a cerebral vein thrombus 2 and over half of the portal vein thrombi. 3 These results suggest that the high SI of venous thrombi on DWI is a characteristic finding. However, the sensitivity and specificity of combined DWI/T 2 -weighted MR imaging were better than those of DWI alone as a screening tool for detecting abdominal malignancies.…”
mentioning
confidence: 78%
“…In one recent study, Sorrentino and colleagues (76) evaluated the diagnostic performance of arterial phase hyperenhancement of the thrombus at CT and found a sensitivity of 87%. As mentioned later, in retrospective studies, diffusion-weighted MR imaging has been shown by some investigators to aid in the differentiation of macrovascular invasion from bland venous thrombus (77), but other investigators have not found diffusion-weighted imaging to be helpful (78). Larger prospective studies are needed to evaluate diffusion-weighted imaging for this purpose.…”
Section: Feature Commentsmentioning
confidence: 99%
“…It should be emphasized, moreover, that ADC and diffusion-weighted signal-intensity ratios are technique, field strength, and scanner dependent; hence, diffusion-weightedbased prediction thresholds may not be generalizable. Additionally, some investigators have suggested that restricted diffusion may aid in the differentiation of macrovascular invasion from bland venous thrombus (77); however, other investigators have found that restricted diffusion does not aid in this differentiation due to substantial overlap in ADCs between bland thrombus and macrovascular invasion (78). Owing to these conflicting results, caution should be exercised in using diffusion-weighted images for differentiating bland from malignant thrombus.…”
Section: Ancillary Features That Favor the Diagnosis Of Malignancy Bumentioning
confidence: 99%
“…8 Discrimination between a benign and malignant etiology for a thrombus may occasionally be difficult despite these differences and the use of modern imaging modalities. 17 Tumor thrombi commonly develop in patients with HCC and RCC, and the surgical approaches to management of such thrombi have been well documented. 5 , 6 , 8 Although less frequently reported, tumor thrombi are also common in patients with pNET.…”
Section: Discussionmentioning
confidence: 99%